Using simulation in assessment and teaching : OSCE adapted for social work - Bogo, Marion; Katz, C. Ellen; Rawlings, Mary; Logie, Carmen H. (CSWE Press, 2014)
This detailed book by the most experienced authors in the field describes how to develop and implement the objective structured clinical examination (OSCE) for social work education. Assessment of student competency is an essential part of social work education. Going beyond the traditional domains for assessing students -- the classroom and field practicums -- the authors offer a new approach that approximates authentic practice tasks: the objective structured clinical examination (OSCE) adapted for social work. Based on the work of two research teams and the extensive experience of the authors, this book provides all the resources necessary for programs to develop and implement the OSCE.